Observed changes in surface air temperature and precipitation in the Hindu Kush Himalayan region over the last 100-plus years - Ren, Yu-Yu; Ren, Guo-Yu; Sun, Xiu-Bao; Shrestha, Arun Bhakta; You, Qing-Long; Zhan, Yun-Jian; Rajbhandari, Rupak; Zhang, Pan-Feng; Wen, Kang-Min (Advances in climate change research, 2017)
In this paper, we analyzed the long-term changes in temperature and precipitation in the Hindu Kush Himalayan (HKH) region based on climate datasets LSAT-V1.1 and CGP1.0 recently developed by the China Meteorological Administration. The analysis results show that during 1901e2014 the annual mean surface air temperature over the whole HKH has undergone a significant increasing trend. We determined the change rates in the mean temperature, mean maximum temperature, and mean minimum temperature to be 0.104 C per decade, 0.077 C per decade, and 0.176 C per decade, respectively. Most parts of the HKH have experienced a warming trend, with the largest increase occurring on the Tibetan Plateau (TP) and south of Pakistan. The trend of precipitation for the whole HKH is characterized by a slight decrease during 1901e2014. During 1961e2013, however, the trend of the annual precipitation shows a statistically significant increase, with a rate of 5.28% per decade and has a more rapid increase since the mid-1980s. Most parts of northern India and the northern TP have experienced a strong increase in the number of precipitation days (daily rainfall 1 mm), whereas Southwest China and Myanmar have experienced a declining trend in precipitation days. Compared to the trends in precipitation days, the spatial pattern of trends in the precipitation intensity seems to be more closely related to the terrain, and the higher altitude areas have shown more significant upward trends in precipitation intensity during 1961e2013.